PENGARUH JENJANG PENDIDIKAN ORANG TUA TERHADAP PRESTASI BELAJAR SISWA DI SMKN 26 JAKARTA - Dinil Abrar Sulthani; Ahmad Murtadho (STIT Al-Marhalah Al-Ulya Bekasi, 2023)
ABSTRACKThis research is related to the level of parental education which discusses the problem of lack of motivation, attention and parenting style of parents to students so that it affects learning achievement obtained in the school environment. The purpose of this study is to analyze and measure how much influence / relationship between the level of education of parents and the learning achievement of students in school. As well as analyzing strategies that parents must use to increase the enthusiasm for learning of students in order to get high learning achievement. Themethod used is descriptive correlational analysis through a quantitative approach using questionnaire instruments distributed to predetermined samples. This study shows that there is an influence on the table of